RESPONSE OF PROTEIN C AND PROTEIN S INHIBITORS IN LONG-TERM ORAL ANTICOAGULANT THERAPY - Mukhlova Montiel, M; Bussey, H (Thrombosis and Haemostasis, 1987)
Protein C (PC) and its coenzyme Protein S (PS) are physiologic inhibitors of activated factors Va and Villa. Deficiency of either one of these inhibitors has been associated with venous thrombosis. Their activity is dependent on vitamin K for hepatic gamma carboxylation and it is depressed during oral anticoagulant therapy. Because rebound thrombosis complicates cessation of anticoagulant therapy, we investigated the response of PC and PS during long term oral anti coagulation. The study encompassed 30 patients ranging between 26 and 76 years of age, who have received therapeutic doses of coumadin from 15 days to more than 8 years. The conditions for which treatment was initiated were deep vein thrombosis, cerebral vascular accidents and cardiac valve replacements.Factor VII and X activity was assayed by one step routine clotting assays. PC antigen (ag), total PSag and free PSag were assayed by Laurel 1 Rocket electroimmunodiffusion method. The measurement of the free PS was carried out after precipitation of C4b-binding protein with polyethylene glycol. PC activity was measured by clotting assay using PC deficient plasma to which was added patient plasma as a source of PC. Control group of 30 individuals in similar age group were assayed parallel with the patient samples. Compared with the control group the coumadin-treated patients showed substantial decrease of all factors studied. Statistical regression analysis of the coumadin group showed a significant increase in PS free (p = 0.014)during long term anti coagulation, while all of the other variables did not change significantly.PCag and total PSag were decreased and their activities, as expected, were more severely affected. The ratio of PC activity to PCag averages 0.39 (normal >0.80) and free PS represented only 27% of the total PSag (normal about 40%). The inhibitors' persistent activity parallels that of the depression of Factors VII and X and there appears to be a balanced coagulation-inhibi-tion system. If PC and PS play a role in rebound thrombosis after a prolonged anticoagulation therapy, the changes may occur after discontinuation of medication.